Heightened sensitivity to the caregiving environment during adolescence: implications for recovery following early‐life adversity. (20th November 2020) - Colich, Natalie L.; Sheridan, Margaret A.; Humphreys, Kathryn L.; Wade, Mark; Tibu, Florin; Nelson, Charles A.; Zeanah, Charles H.; Fox, Nathan A.; McLaughlin, Katie A.
Abstract : Background: Adolescence has been proposed to be a period of heightened sensitivity to environmental influence. If true, adolescence may present a window of opportunity for recovery for children exposed to early‐life adversity. Recent evidence supports adolescent recalibration of stress response systems following early‐life adversity. However, it is unknown whether similar recovery occurs in other domains of functioning in adolescence. Methods: We use data from the Bucharest Early Intervention Project – a randomized controlled trial of foster care for children raised in psychosocially depriving institutions – to examine the associations of the caregiving environment with reward processing, executive functioning, and internalizing and externalizing psychopathology at ages 8, 12, and 16 years, and evaluate whether these associations change across development. Results: Higher quality caregiving in adolescence was associated with greater reward responsivity and lower levels of internalizing and externalizing symptoms, after covarying for the early‐life caregiving environment. The associations of caregiving with executive function and internalizing and externalizing symptoms varied by age and were strongest at age 16 relative to ages 8 and 12 years. This heightened sensitivity to caregiving in adolescence was observed in both children with and without exposure to early psychosocial neglect. Conclusions: Adolescence may be a period of heightened sensitivity to the caregiving environment, at least for some domains of functioning. For children who experience early psychosocial deprivation, this developmental period may be a window of opportunity for recovery of some functions. Albeit correlational, these findings suggest that it may be possible to reverse or remediate some of the lasting effects of early‐life adversity with interventions that target caregiving during adolescence.